2015
DOI: 10.1021/acs.iecr.5b01862
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Simulation and Proposed Optimization of the Pressure Swing Adsorption Process for N2/CH4 Separation under External Disturbances

Abstract: This work presents a detailed study of the systematic simulation, optimization, and control of a pressure swing adsorption (PSA) process that used activated carbon as adsorbent to recover CH 4 from a gas mixture (70% N 2 /30% CH 4 ). The state-of-the-art reduced space successive quadratic-programming (r-SQP) optimization algorithm is employed to find the optimal values of the decision variables with additional constraints. The best closed loop recovery obtained for the PSA system under consideration is around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Adsorption by using porousm aterials to removeC O 2 has gained widespread attention recently owing to its economic and environmental advantages. [4][5][6] Accordingly,s creening suitable adsorbents with high selectivity and adsorption capacity as well as low regeneration costs is vital in achieving the separation processes with excellent overall performances. [7] To date, carbonaceous materials, [8][9][10] metal-organic frameworks (MOFs), [11][12][13] and zeolites [14][15][16][17][18] are three typical categories of candidates for CO 2 /CH 4 and CO 2 /N 2 separations.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption by using porousm aterials to removeC O 2 has gained widespread attention recently owing to its economic and environmental advantages. [4][5][6] Accordingly,s creening suitable adsorbents with high selectivity and adsorption capacity as well as low regeneration costs is vital in achieving the separation processes with excellent overall performances. [7] To date, carbonaceous materials, [8][9][10] metal-organic frameworks (MOFs), [11][12][13] and zeolites [14][15][16][17][18] are three typical categories of candidates for CO 2 /CH 4 and CO 2 /N 2 separations.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there have only been two PSA studies which include feedback control. Sun et al developed a PID controller for a 3‐bed, vacuum PSA system used for separation of methane from nitrogen . They proposed a PID controller which maintains the methane product purity by manipulating the adsorption step duration while the other step durations were either fixed or were a fixed multiple of the adsorption step duration They use this closed‐loop system to optimize the PSA operation.…”
Section: Background Information and Existing Literaturementioning
confidence: 99%
“…A comparison between PID and MPC is necessary in the RPSA system because it demonstrates the superior performance a multivariable controller has over more conventional options. Like other PSA control studies, a discrete SISO PID controller was implemented on the RPSA model which utilizes proportional, integral, and derivative action to make control actions. The SISO PID controls only the product oxygen concentration by manipulating only the adsorption time, and the tank pressure is not controlled.…”
Section: Controller Performance and Disturbance Studiesmentioning
confidence: 99%
“…Nevertheless, the existing systematic optimization studies have shown that the calculation expense based on SD method was too high due to the large amount of sensitivity matrix calculation. [4][5][6][7][8] In this regard, more attention has been paid to the optimization framework based on FD method in recent years.…”
Section: Introductionmentioning
confidence: 99%